ASAH1‐related disorders: Description of 15 novel pediatric patients and expansion of the clinical phenotype. Issue 6 (2nd September 2020) - Mahmoud, Iman G.; Elmonem, Mohamed A.; Zaki, Maha S.; Ramadan, Areef; Al‐Menabawy, Nihal M.; El‐Gamal, Aya; Mansour, Lobna; Issa, Mahmoud Y.; Abdel‐Hamid, Mohamed S.; Abdel‐Hady, Sawsan; Khalifa, Iman; Ibrahim, Ahmed; et al.
Abstract: Acid ceramidase deficiency is an orphan lysosomal disorder caused by ASAH1 pathogenic variants and presenting with either Farber disease or spinal muscle atrophy with progressive myoclonic epilepsy (SMA‐PME). Phenotypic and genotypic features are rarely explored beyond the scope of case reports. Furthermore, the new biomarker C26‐Ceramide requires validation in a clinical setting. We evaluated the clinical, biomarker and genetic spectrum of 15 Egyptian children from 14 unrelated families with biallelic pathogenic variants in ASAH1 (12 Farber and 3 SMA‐PME). Recruited children were nine females/six males ranging in age at diagnosis from 13 to 118 months. We detected ASAH1 pathogenic variants in all 30 alleles including three novel variants (c.1126A>G (p.Thr376Ala), c.1205G>A (p.Arg402Gln), exon‐5‐deletion). Both total C26‐Ceramide and its trans‐ isomer showed 100% sensitivity for the detection of ASAH1 ‐related disorders in tested patients. A 10‐year‐old girl with the novel variant c.1205G>A (p.Arg402Gln) presented with a new peculiar phenotype of PME without muscle atrophy. We expanded the phenotypic spectrum of ASAH1 ‐related disorders and validated the biomarker C26‐Ceramide for supporting diagnosis in symptomatic patients. Abstract :